2014
DOI: 10.5858/arpa.2013-0371-oa
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inflammatory (Lymphoepithelioma-like) Hepatocellular Carcinoma: A Study of 8 Cases

Abstract: Context.-The World Health Organization has recently recognized lymphoepithelioma-like carcinoma, or inflammatory hepatocellular carcinoma, as a variant of hepatocellular carcinoma.Objective.-To identify and characterize the inflammatory hepatocellular carcinomas in our institution from 1988 to the present.Design.-All cases of hepatocellular carcinoma in our institution from 1988 to the present were reviewed and reclassified as lymphoepithelioma-like carcinoma and were studied in comparison to appropriately mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 47 publications
0
41
1
Order By: Relevance
“…Interestingly, they were particularly frequent in the so‐called lymphoepithelioma‐like subtype of HCC. This uncommon histological variant, the pathogenesis of which is unknown, is characterized by sheets of neoplastic cells intermingled with a dense inflammatory stroma . Immunohistochemical studies have shown that this stroma is mainly made of cytotoxic T cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, they were particularly frequent in the so‐called lymphoepithelioma‐like subtype of HCC. This uncommon histological variant, the pathogenesis of which is unknown, is characterized by sheets of neoplastic cells intermingled with a dense inflammatory stroma . Immunohistochemical studies have shown that this stroma is mainly made of cytotoxic T cells .…”
Section: Discussionmentioning
confidence: 99%
“…This uncommon histological variant, the pathogenesis of which is unknown, is characterized by sheets of neoplastic cells intermingled with a dense inflammatory stroma. (17,27) Immunohistochemical studies have shown that this stroma is mainly made of cytotoxic T cells. (28,29) Unlike other lymphoepithelioma-like carcinomas arising in other organs, no link with Epstein-Barr virus infection has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostains are typically needed to confi rm hepatocellular differentiation; a panel of immunostains for glypican-3, HepPar1, and arginase-1 can be helpful. The reactive lymphocytes are primarily T cells [ 96 ]. Also of note, the epithelial component in lymphoepithelioma-like cholangiocarcinoma is typically EBV positive, while the epithelial component in both lymphoepithelioma-like hepatocellular carcinoma and in lymphocyterich hepatocellular carcinoma is EBV negative [ 92 , 95 , 96 ], with the exception of one case report [ 97 ].…”
Section: Defi Nitionmentioning
confidence: 99%
“…Previously known as lymphoepithelioma-like HCC, lymphocyte-rich HCC is characterized by an immune-rich stroma [19,20] . Wada et al [21] defined this subtype by the presence of more than 100 tumorinfiltrating lymphocytes in 10 high-power fields.…”
Section: Lymphocyte-rich Hccmentioning
confidence: 99%